Producto Turístico Cultural Integrado Conociendo la Villa Blanca en tiempo de Parranda - Menéndez Rodríguez, Luis Angel (Universidad Central "Marta Abreu" de Las Villas, 2013)
El turismo constituye pilar de desarrollo económico y social, aumentando continuamente desde los años cincuenta hasta nuestros días. Hoy el sector turístico se encuentra en un periodo de cambios en cuanto a las motivaciones y las tendencias turísticas. Por lo que el turismo cultural se convierte en un ente protagónico como modalidad imponiéndose como una de las modalidades que va teniendo un crecimiento acelerado de la demanda global en estos tiempos; por tanto la presente investigación se centra en la elaboración de una propuesta de producto turístico cultural integrado que contiene los recursos culturales de la Parranda y la culinaria tradicional y el Patrimonio Local en el destino Caibarién promoviéndolo como destino cultural, favoreciendo su puesta en valor. Fueron analizados varios procedimientos para el diseño de productos resultando ser seleccionados el procedimiento participativo para el diseño de productos turísticos integrados propuesto por Machado (2011).

The tourism constitutes pillar of economic and social development, increasing continually from the years fifty until our days. Today the tourist sector is in a period of changes as for the motivations and the tourist tendencies. For what the cultural tourism becomes a protagonistic entity as modality, imposing you like one of the modalities that goes having a quick growth of the global demand in these times; therefore, the present investigation is centered in the elaboration of a proposal of integrated cultural tourist product that it contains the cultural resources of the Spree and the culinary one traditional and the local patrimony in the destination Caibarién promoting him like cultural destination, favoring its setting in value. The Integrated Cultural Tourist Product Knowing the Villa Blanca in time of Spree could be possible to the application of the procedure of diagnosis of the tangible and intangible patrimonial tourist resources proposed by Carvajal (2008) to locate and to analyze each resource belonging to this traditional festivity, and to the elements of the culinary one and the tangible patrimony of the destination that are part of the product. Several procedures were also analyzed for the design of products; being to be selected the procedure participative for the design of integrated tourist products proposed by Machado (2011). The main value of the present investigation is necessary since it is in agreement with the limits of the Economic and Social Politics of the Party and the Revolution, fulfilling the necessity of creating novel and varied tourist offers.
Keywords: Turismo Cultural; Patrimonio Cultural; Producto Turístico Cultural; Parranda; Culinaria Tradicional; Turismo; Tourism